(untitled) (Annals of Medical Research, 2021)
Aim: Having a healthy child is the most basic concern for parents, and their children being ill or showing signs of illness therefore causes them anxiety. Parents cannot generally be objective in assessing the growth of their own children. Children’s growth must be evaluated solely with appropriate measurements and assessment criteria. The purpose of this study is to investigate the growth of patients with suspected retarded growth presenting to the children’s health and diseases clinic.